Climate change and land suitability for potato production in England and Wales: impacts and adaptation - Daccache, Andre; Keay, Caroline A.; Jones, Robert J. A.; Weatherhead, E. K.; Stalham, M. A.; Knox, Jerry W. (Cambridge University Press, 2012)
The viability of commercial potato production is influenced by spatial and temporal variability in soils and agroclimate, and the availability of water resources where supplemental irrigation is required. Soil characteristics and agroclimatic conditions greatly influence the cultivar choice, agronomic husbandry practices and the economics of production. Using the latest (UKCP09) scenarios of climate change for the UK, this paper describes a methodology using pedo-climatic functions and a GIS to model and map current and future land suitability for potato production in England and Wales. The outputs identify regions where rainfed production is likely to become limiting and where future irrigated production would be constrained due to shortages in water availability. The results suggest that by the 2050s, the area of land that is currently well or moderately suited for rainfed production would decline by 74 and 95% under the "most likely" climate projections for the low and high emissions scenario respectively, owing to increased droughtiness. In many areas, rainfed production would become increasingly risky. However, with supplemental irrigation, around 85% of the total arable land in central and eastern England would remain suitable for production, although most of this is in catchments where water resources are already over-licensed and/or over-abstracted; the expansion of irrigated cropping is thus likely to be constrained by water availability. The increase in volumetric water demand due to the switch from rainfed to irrigated potato cropping is likely to be much greater than the incremental increase in water demand solely on irrigated potatoes. The implications of climate change on the potato industry, the adaptation options and responses available, and the uncertainty associated with the land suitability projections, are discussed.